PENINGKATAN DAYA SAING IKM BATIK TULIS PENDUKUNG IMPLEMENTASI ONE VILLAGE ONE PRODUCT (OVOP) - Ida Kusnawati Tjahjani; Mochammad Hatta; Dedy Kunhadi; Purwanto Purwanto (Universitas Muhammadiyah Mataram, 2020)
Abstrak: Program Pengembangan Produk Unggulan Daerah (PPPUD) ini merupakan kegiatan lanjutan dari Program Kemitraan Masyarakat (PKM) yang telah dilaksanakan tahun 2019. Dari observasi dan wawancara, teridentifikasi masalah pada 3 bidang, yaitu Produksi, Manajemen, dan Sumber Daya Manusia (SDM). Berbagai kegiatan dirancang untuk tujuan: 1) peningkatan hasil produksi; 2) memiliki merek dagang resmi dari Dinas Perindustrian dan Perdagangan; 3) peningkatan keahlian dan kompetensi SDM di bidang produksi dan manajeman; 4) teridentifikasinya lebih banyak motif khas Sekardangan; 5) lebih dikenalnya batik tulis Sekardangan; 6) peningkatan daya saing pengrajin; 7) eksistensi batik tulis Sekardangan; 8) mendukung implementasi program OVOP yang telah ditetapkan. Metode pelaksanaan kegiatan, meliputi; 1) observasi dan wawancara; 2) identifikasi masalah, 3) pengambilan data: FGD dengan para ahli di bidangnya; 4) mendesain ulang (inovasi) beberapa peralatan membatik, 5) membuat modul pelatihan, 6) pelatihan dan pendampingan; 7) pembuatan laporan hasil pelatihan, laporan kemajuan, laporan akhir dan laporan keuangan, 8) publikasi media massa online; 10) Youtube; 11) pembuatan artikel jurnal nasional ber-ISSN; 12) pendaftaran HKI; 13) pembuatan buku referensi. Hasil pelaksanaan kegiatan adalah terwujudnya semua target kegiatan, terjalin kerja sama yang baik dan berkelanjutan serta peningkatan daya saing batik tulis sebagai produk unggulan daerah.Abstract: The Regional Superior Product Development Program (PPPUD) is a continuation of the Community Partnership Program (PKM) which has been implemented in 2019. From observations and interviews, identified problems in 3 areas, namely Production, Management, and Human Resources (HR). Various activities are designed for the purpose of: 1) increased production; 2) has an official trademark from the Industry and Trade Office; 3) increased expertise and competence of human resources in the field of production and management; 4) identification of more typical motifs Sekardangan; 5) better known Sekardangan batik; 6) increasing the competitiveness of craftsmen; 7) the existence of Sekardangan handmade batik; 8) supports the implementation of predetermined OVOP programs. Methods of carrying out activities, including; 1) observation and interview; 2) identification of problems, 3) data collection: FGD with experts in their fields; 4) redesigning (innovation) some batik equipment; 5) making training modules; 6) training and mentoring; 7) making training report, progress report, final report and financial report; 8) online mass media publication; 10) Youtube; 11) preparation of ISSN national journal articles; 12) registration of IPR; 13) making reference books. The results of the implementation of the activities are the realization of all activity targets, good and sustainable cooperation established as well as increasing the competitiveness of written batik as a regional superior product.